Off-label use of Woven EndoBridge device in vertebro-basilar junction aneurysm and a review of the literature - Shail Thanki; Hannah Goldman-Daleo; Kunal Vakharia (Brain Hemorrhages, 2023)
An intrasaccular flow diverter, the Woven EndoBridge device has emerged as an alternate intervention for complex aneurysms of the ACA, MCA, ICA, and basilar artery. However, few studies report the use of the WEB device in off-label locations. This case report aims to contribute to this limited collection of data. We present a case of a 53-year-old male presenting with occipital headaches, found to have vertebrobasilar junction aneurysm. The WEB device was successfully used to embolize a large aneurysm of the vertebrobasilar junction, a current off-label location. This represents a new use of the WEB device, as well as an approach that addresses the limitations of other techniques used for vertebrobasilar junction aneurysms.